2006
DOI: 10.1143/jjap.45.l683
|View full text |Cite
|
Sign up to set email alerts
|

Current-Excited Magnetization Dynamics in Narrow Ferromagnetic Wires

Abstract: We investigate the current-excited magnetization dynamics in a narrow ferromagnetic Permalloy wire by means of Lorentz microscopy, together with the results of simultaneous transport measurements. A detailed structural evolution of the magnetization is presented as a function of the applied current density. Local structural deformation, bidirectional displacement, and magnetization reversal are found below the Curie temperature with increasing the current density. We discuss probable mechanisms of observed fea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
38
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 32 publications
(52 reference statements)
1
38
1
Order By: Relevance
“…Extensive experimental [1][2][3] and theoretical 4,5 studies have shown that a current on the order of 10 5 -10 8 A cm − 2 is capable of moving the conventional MDW or magnetic vortex in ferromagnetic (FM) nanostructures. However, such high current densities should induce the intense joule heating, which is detrimental for practical applications.…”
mentioning
confidence: 99%
“…Extensive experimental [1][2][3] and theoretical 4,5 studies have shown that a current on the order of 10 5 -10 8 A cm − 2 is capable of moving the conventional MDW or magnetic vortex in ferromagnetic (FM) nanostructures. However, such high current densities should induce the intense joule heating, which is detrimental for practical applications.…”
mentioning
confidence: 99%
“…Current-induced DW motion is of particular interest because it enables the position of DW to be controlled electrically without applying an external magnetic field [1][2][3][4][7][8][9][10][11][12][13][14][16][17][18][19][20][21] . The electric field effect on magnetic materials has been actively studied recently, because magnetic properties can be controlled electrically [22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37] , when a field-effect-device structurethat is, one consisting of a top-gate electrode, a dielectric insulator layer (or a liquid electrolyte), and a ferromagnetic layer-is used to modulate a carrier density.…”
mentioning
confidence: 99%
“…It has been demonstrated that domain walls can be moved not only by a magnetic field but also by an electric current [4,[6][7][8][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Since novel applications based on the domain wall motion have been proposed [25][26][27][28], the study of dynamics of a magnetic domain wall in a magnetic nanowire is of importance not only from the viewpoints of exciting fundamental physics but also from technological points of view.…”
mentioning
confidence: 99%